Menstrual product choice and the extent of period poverty among young adult females: findings from a cross-sectional study in Kerala, India - S. K., Godwin; Ullas C. U., Lakshmi; V. M., Anjana; G. K., Mini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In Kerala state, India, while there is higher coverage of hygienic methods for menstrual protection among young women, empirical evidence on menstrual hygiene management is limited. This study aims to present menstrual hygiene product choices and the extent of period poverty among young adult females in Kerala. Methods: A cross-sectional study was conducted in Kerala using a web-based Google form. Data were collected on menstrual product usage, perceptions and attitudes towards menstruation, awareness and use of government initiatives for menstrual hygiene management, perspectives on better management, period poverty, and associated factors. Results: The mean age of respondents was 21.7 years (SD±2.0). Cultural beliefs hindered the choice of menstrual products. Period poverty was reported by 25.5% of respondents, with higher rates among younger, lower social category, and unemployed individuals. Lower income and negative attitudes towards menstruation were significantly associated with higher period poverty. Conclusions: There is a need for free menstrual products for the financially disadvantaged. Further research is necessary to gain a comprehensive understanding of period poverty in this community.